Thea Stilton and the secret of the old castle - Brandi, Jacopo, 1971-; Clement, Emily (Translator).; Dami, Elisabetta (New York : Scholastic, 2012)
"When the Thea Sisters' friend Bridget returns to Scotland for a family emergency, the five mice offer to help. And when Bridget goes missing, they have to rush to Scotland to find her! Along the way, the Thea Sisters encounter Celtic legends, cryptic messages, and hidden treasures on a trip that's full of surprises!"--P. [4] of cover.
"Based on an original idea by Elisabetta Dami"--T.p. verso.
RL3.
007-010.
Keywords: Mice -- Juvenile fiction; Missing persons -- Juvenile fiction; Mice -- Fiction; Missing persons -- Fiction; Mystery and detective stories; Mice -- Fiction; Kidnapping -- Fiction; Scotland -- Juvenile fiction; Scotland -- Fiction; Scotland -- Fiction; Mystery fiction